New occurrences and biological aspects to four species of rodents (Mammalia: Cricetidae) from Brazil - Machado, Felipe Santana; Lima, Ivan Junqueira; Lopes, Arina Pacheco Magalhães; Moura, Aloysio Souza de; Abreu, Thamíris Christina Karlovic de (Revista Agrogeoambiental, 2015)
The most representative group among mammals are rodents for presenting high ratio to the total of species. However, rodents are considered a "taxonomic chaos" and some species such as Blarinomys breviceps, Bibimys labiosus, Akodon lindberghi and Pseudoryzomys simplex are little known. That can be explained because of low occurrence of small terrestrial mammals in wildlife inventories and/or reduced abundance. The objective is to describe the occurrence of these species and analyze these locations presenting descriptive comments about their biological aspects. Therefore, in addition to specimens collected in the field, some scientific collections were visited and reviews in relevant literature were conducted in order to obtain information about the locations and biological aspects. Akodon lindberghi was found in five sites, Bibimys labiosus was found in 15, Blarinomys breviceps in 39 and Pseudoryzomys simplex in 13. Each species has specific information and they are included in two threatened areas, Atlantic Forest and Cerrado. The occurrences are disconnected and related to taxonomic and methodological problems. Keywords: New records. Rodentia. Sigmodontinae. Occurence area.